Carbonate fabrics in the modern microbialites of Pavilion Lake: two suites of microfabrics that reflect variation in microbial community morphology, growth habit, and lithification. Issue 4 (26th March 2015) - Theisen, C. Harwood; Sumner, D. Y.; Mackey, T. J.; Lim, D. S. S.; Brady, A. L.; Slater, G. F.
Abstract Modern microbialites in Pavilion Lake, BC, provide an analog for ancient non‐stromatolitic microbialites that formed from in situ mineralization. Because Pavilion microbialites are mineralizing under the influence of microbial communities, they provide insights into how biological processes influence microbialite microfabrics and mesostructures. Hemispherical nodules and micrite–microbial crusts are two mesostructures within Pavilion microbialites that are directly associated with photosynthetic communities. Both filamentous cyanobacteria in hemispherical nodules and branching filamentous green algae in micrite–microbial crusts were associated with calcite precipitation at microbialite surfaces and with characteristic microfabrics in the lithified microbialite. Hemispherical nodules formed at microbialite surfaces when calcite precipitated around filamentous cyanobacteria with a radial growth habit. The radial filament pattern was preserved within the microbialite to varying degrees. Some subsurface nodules contained well‐defined filaments, whereas others contained only dispersed organic inclusions. Variation in filament preservation is interpreted to reflect differences in timing and amount of carbonate precipitation relative to heterotrophic decay, with more defined filaments reflecting greater lithification prior to degradation than more diffuse filaments. Micrite–microbial crusts produce the second suite of microfabrics and form in association with filamentous green algae oriented perpendicular to the microbialite surface. Some crusts include calcified filaments, whereas others contained voids that reflect the filamentous community in shape, size, and distribution. Pavilion microbialites demonstrate that microfabric variation can reflect differences in lithification processes and microbial metabolisms as well as microbial community morphology and organization. Even when the morphology of individual filaments or cells is not well preserved, the microbial growth habit can be captured in mesoscale microbialite structures. These results suggest that when petrographic preservation is extremely good, ancient microbialite growth structures and microfabrics can be interpreted in the context of variation in community organization, community composition, and lithification history. Even in the absence of distinct microbial microfabrics, mesostructures can capture microbial community morphology.